Ocean warming (OW) and freshening influence metabolism and cellular damage in Loxechinus albus at the extremes of their Patagonian distribution - Paola A. Villanueva; Jorge M. Navarro; Sebastián Cook; Danae Paredes; Joseline Büchner-Miranda; Eduardo Ramírez-Kuschel; Ignacio Echeverría; Víctor M. Cubillos; Carlos Lara; Marcela Astorga (Marine Pollution Bulletin, 2026)

Food Security Outcomes and Postintervention Experiences in a Produce Prescription Pilot: A Mixed-Methods Study - Caroline E. Owens; Miranda Cook; Tammy Reasoner; Aleta McLean; Amy Elsasser; Ciara Long; Amy Webb Girard (Journal of Nutrition Education and Behavior, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Metabolic and survival responses of the carnivorous snail Acanthina monodon to extreme marine heatwaves - Paola A. Villanueva; Joseline A. Büchner-Miranda; Jorge M. Navarro; Sebastián Cook; Octavio Mercado-Peña; Paula Amador-Véliz; Gonzalo Donoso; Elisabeth Teca Oliva; Oscar R. Chaparro (Regional Studies in Marine Science, 2025)

MLH1 c.27G>A (p.Arg9=) is a synonymous likely/pathogenic variant underlying variably mosaic constitutional MLH1 methylation in Lynch syndrome - Rocio Alvarez; Paula Climent-Cantó; GiWon Shin; Francesca Paola Aguirre; Lisa Zhou; Dennis J. Hazelett; Brent K. Larson; Covadonga Vara; Gabriel Capellá; Víctor Lorca Castellanos; Pilar Garre Rubio; Françoise Desseigne; et al. (Familial Cancer, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Diagnosis and treatment of an oral, migrating foreign body penetrating the spinal cord in a rabbit (Oryctolagus cuniculus) - Margaret Cook; Amanda L. Day; Catriona MacPhail; Becky Pacheco; Anna Price; Camilla Cooper; Kelly Hall; Alex Ohlendorf; Miranda J. Sadar (Journal of Exotic Pet Medicine, 2024)